Pengelolaan Keuangan Desa di Desa Definitif Tahun 2018 - Yusriansyah Yusriansyah; Dede Sri Kartini; Neneng Yani Yuningsih (ARISTO, 2021)
The provision of financial assistance from the State Budget (APBN) or called the Village Fund is one of the additional sources of village income in Indonesia. The funding assistance was realized by the Government Ir. Joko Widodo and Drs.Jusuf Kalla in order to implement the nawacita that is contained in the third point, namely the desire of the Indonesian government to carry out equitable development in the periphery with the concept of strengthening villages and regions in Indonesia, with the large amount of village income then needs to be utilized effectively and efficiently using funds through good management of village finances. The basic rule that forms the basis of the implementation of the village financial management policy is Government Regulation Number 43 of 2014 concerning the implementation of Law Number 6 of 2014 concerning Villages. The process of village financial management from a series of planning activities to accountability is carried out over a period of one year as stated in the Minister of Domestic Affairs regulation No. 113 regarding village financial management. The results showed that the Batu Timbau Ulu Village in the management of village funds and the allocation of village funds was considered to be inadequate in the process of planning a number of activities to be carried out, as evidenced by a number of existing activities, almost 41.39% was used for village government administration expenses, while activities such as physical development, community empowerment and community development only get a portion of 58.61%. Furthermore, the government of Batu Timbau Ulu Village in the implementation of village financial management experienced constraints in the form of the non-liquidation of the Village Fund Allocation Budget Phase IV so that some activities were forced to not be carried out. Furthermore, the administration, reporting and accountability activities have been carried out properly.